A structure-based designed small molecule depletes hRpn13Pru and a select group of KEN box proteins - Xiuxiu Lu; Monika Chandravanshi; Venkata R. Sabbasani; Snehal Gaikwad; V. Keith Hughitt; Nana Gyabaah-Kessie; Bradley T. Scroggins; Sudipto Das; Wazo Myint; Michelle E. Clapp; Charles D. Schwieters; Marzena A. Dyba; et al. (Nature Communications, 2024)
Abstract Proteasome subunit hRpn13 is partially proteolyzed in certain cancer cell types to generate hRpn13Pru by degradation of its UCHL5/Uch37-binding DEUBAD domain and retention of an intact proteasome- and ubiquitin-binding Pru domain. By using structure-guided virtual screening, we identify an hRpn13 binder (XL44) and solve its structure ligated to hRpn13 Pru by integrated X-ray crystallography and NMR to reveal its targeting mechanism. Surprisingly, hRpn13Pru is depleted in myeloma cells following treatment with XL44. TMT-MS experiments reveal a select group of off-targets, including PCNA clamp-associated factor PCLAF and ribonucleoside-diphosphate reductase subunit M2 (RRM2), that are similarly depleted by XL44 treatment. XL44 induces hRpn13-dependent apoptosis and also restricts cell viability by a PCLAF-dependent mechanism. A KEN box, but not ubiquitination, is required for XL44-induced depletion of PCLAF. Here, we show that XL44 induces ubiquitin-dependent loss of hRpn13Pru and ubiquitin-independent loss of select KEN box containing proteins.